Polycrystalline Materials Theoretical and Practical Aspects - Todorov Zachariev, Zachary (IntechOpen, 2012)
The book "Polycrystalline Materials - Theoretical and Practical Aspects" is focused on contemporary investigations of plastic deformation, strength and grain-scale approaches, methods of synthesis, structurals, properties, and application of some polycrystalline materials. It is intended for students, post-graduate students, and scientists in the field of polycrystalline materials.